THE USE OF POPULAR SONGS TO IMPROVE THE NARRATIVE TEXT LISTENING SKILL OF THE TENTH GRADERS OF SMA TARAKANITA MAGELANG IN THE SCHOOL YEAR 2018/2019 - Aldino Anjas Bagaskara (Faculty of Education and Teachers Training, 2020)
THE USE OF POPULAR SONGS TO IMPROVE THE NARRATIVE TEXT LISTENING SKILL OF THE TENTH GRADERS OF SMA TARAKANITA MAGELANG IN THE SCHOOL YEAR 2018/2019 Aldino Anjas BagaskaraEnglish Education Department, Faculty of Education and Teachers TrainingTidar Universityaldinoanjas@gmail.com ABSTRACT Listening is one of the four language skills that is taught in junior and senior high school. However, the students’ listening skill is still far from the learning target. It can be seen from the semester test result of the tenth graders of SMA Tarakanita Magelang in the academic year of 2018/2019. The students’ average score was 58. This score is less than 75 which is the minimum standard score of learning target.There are two objectives of this research. First, it is to know how great can the use of Popular Songs can improve students’ learning motivation of narrative text listening skill of the tenth graders of SMA Tarakanita Magelang in the school year 2018/2019. Second, it is to know how great is the improvement of using Popular Songs in teaching students’ listening skill of narrative text of the tenth graders of SMA Tarakanita Magelang in the school year 2018/2019.The writer conducted a classroom action research by using popular songs in teaching narrative text listening. The writer took class X IPS of SMA Tarakanita Magelang as the subject of the research. The writer found that the use of popular songs can increase the students’ learning motivation. The observation percentage in Pre-Cycle is 55% and it becomes 88% in Cycle II. The total improvement is 33%. The use of Popular Songs also makes improvement in listening test. In Pre-Cycle test, the average score of listening narrative text is 59.4. After the writer applied popular songs, the students’ average score in Cycle I is 63 while in Cycle II it reaches 81. The improvement from Pre Cycle test to Cycle I test is 4 points, and from Cycle I test to Cycle II test is 18 points. Overall the total improvement from Pre-cycle test to Cycle II test is 22 points.Based on the above explanation, the writer concludes that the use of popular songs can improve the learning motivation of the narrative text listening skill. The writer suggests English teachers to use popular songs as an alternative way of teaching listening in senior high school. To overcome the weakness of this technique, the teacher should prepare the right song that student’s hear a lot in order accomplished is objectives of the research and teacher also should give much attention to the students who are weak in listening English.Keyword: Popular Songs, narrative text, learning motivation.